Leveraging the placenta to advance neonatal care - Mestan, Karen K.; Leibel, Sandra L.; Sajti, Eniko; Pham, Betty; Hietalati, Samantha; Laurent, Louise; Parast, Mana (Frontiers in Pediatrics, 2023)
The impact of placental dysfunction and placental injury on the fetus and newborn infant has become a topic of growing interest in neonatal disease research. However, the use of placental pathology in directing or influencing neonatal clinical management continues to be limited for a wide range of reasons, some of which are historical and thus easily overcome today. In this review, we summarize the most recent literature linking placental function to neonatal outcomes, focusing on clinical placental pathology findings and the most common neonatal diagnoses that have been associated with placental dysfunction. We discuss how recent technological advances in neonatal and perinatal medicine may allow us to make a paradigm shift, in which the valuable information provided by the placenta could be used to guide neonatal management more effectively, and to ultimately enhance neonatal care in order to improve our patient outcomes. We propose new avenues of clinical management in which the placenta could serve as a diagnostic tool towards more personalized NICU management.